The handbook of environmental health - Spellman, Frank R. (Scarecrow Press, Inc., 2013)
"Environmental issues, global warming, pollution, and chemical dumping, are ever present in the news. But what about the health problems these issues pose? Frank Spellman and Melissa Stoudt identify the hazardous environmental issues and explain the science behind the dangers to our health. The Handbook of Environmental Health begins with defining the most commonly used terms, clearly explained for any student to learn and understand. Then each chapter tackles a different issue, outlining its scientific concepts and relating it to our health, with case studies or scenarios to bring the concepts to life. Lastly, the chapters conclude with thought-provoking questions. The authors also provide solutions to control the factors that harm our health, making this handbook a valuable resource for any student, library, or one interested in the dangers of environmental health"--Provided by publisher.